Ministrorum Institutio: Aposolic Letter Issued Motu Proprio, whereby the Apostolic Constitution Pastor Bonus is Modified and Responsibility for Seminaries is transferred from the Congregation for Catholic Education to the Congregation for the Clergy - Benedikt, XVI., Papst (Roman Replies and CLSA Advisory Opinions 2013, 2013)
Whereby the Apostolic Constitution Pastor Bonus is modified and responsibility for seminaries is transferred from the congregation for catholic education to the congregation for the clergy.